Kontemplasi Diri Dalam Lukisan - -, Syamsiar (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2014)
Creating works on the theme of contemplation themselves in my paintings come from my series of contemplative experience in life that are particularly religious. That is an afterthought to an essential aspect of my life, that I experienced a wide range of activities, observe and biodiversity during the past and the present are associated with signs of the presence or existence of God in the mystery of life that I live everyday. The formulation of the concept of self-creation is a religious contemplation as a means to achieve harmony, harmony and happiness in life. Creation method using the theory of the creation process LHChapman among others 1). Efforts to find an idea (the inception of an idea) or find a source of ideas, inspiration or inspiration, 2). Enhance, develop, and establish initial ideas (elaboration and refinement), 3) .Visualisasi into the medium (heention in a medium) .Media to be used in the embodiment of the works are oil on kanvas.Subject matter in creating works rooted in reflection of contemplation myself among others: drapery (Inside the cloth) and other subjects such as a series of letters of the Arabic alphabet, clouds, light and so forth as a visual form to affirm the meaning of the painting.Keywords: self-contemplation, the creation of art, paintings